Electronic structure, optical, thermoelectric and magnetic properties of A2CdP2 (A = Ca, Sr and Ba) n-type narrow band gap semiconductors. (May 2022) - Aman, Salma; Albalawi, Hind; Tahir Farid, Hafiz Muhammad; Mahmoud, Khaled H.; El-Bahy, Zeinhom M.
Abstract: Structural, Optoelectronic, thermoelectric and magnetic properties of A2 CdP2 (A = Ca, Sr and Ba) Zentl phase compounds in Cmc21 symmetry are investigated using FP-LAPW method with GGA-PBE, GGA-PBEsol, HSE06, G0 W0 and GGA-mBJ potentials based on DFT. Estimated structure parameters are well agreement with the experiment. Cohesive energy shows that Ba2 CdP2 is more stale then the rest compounds and posses high melting point. Electronic properties shows that all the compounds are direct band gap semiconductors at central symmetry while GGA-mBJ transit the direct band gap nature to indirect nature at ᴦ-H symmetry. The direct band gap values are ranging from 0.74 to 1.47 eV. The calculated band gaps are decreasing with the cation replacement and increasing by hybrid functionals. The result revel that all the compounds are optically active in infrared region of electromagnetic spectrum. Optical properties reveals that these compounds can be used as potential candidate for optoelectronic devices. Due to the narrow band gap semiconducting nature of these compounds their thermoelectric parameters are also calculated which shows that these compounds are efficient to use as the active thermoelectric materials. DFT and Post-DFT calculation indicate the paramagnetic nature of all compounds.